Treating self-harm behaviors in prisons: implementation of the STEPPS program - Rosa Lorente-Català; Irene Jaén; Xavier Buscà-Huertas; Berta Framis; Azucena García-Palacios (BMC Psychology)
Abstract Background Improving mental health within correctional facilities, specifically to address self-harm behaviors, is a crucial endeavor. However, significant challenges arise when implementing evidence-based programs within this complex setting. Despite these hurdles, the Systems Training for Emotional Predictability and Problem Solving (STEPPS) program has garnered recognition, notably in the United States, for its efficacy in tackling such issues. This study aimed to examine inmate profiles in prisons located in Catalonia, Spain, and to investigate the STEPPS program’s effectiveness and implementation process. Method Forty-one inmates participated in the study and completed measures covering self-harm behaviors, emotion regulation, impulsivity, mental health symptoms, and satisfaction with the intervention. Twenty-four professionals who implemented the STEPPS program completed satisfaction, normalization process, burnout, acceptability, appropriateness, and feasibility measures. Results The results suggest that the STEPPS program significantly reduced symptoms of emotional dysregulation, motor impulsivity, and compulsive symptomatology among inmates. The intervention was well-received by professionals, and perceived as appropriate and feasible. The perception of feasibility decreased after implementation, likely due to contextual factors such as inmate and organization characteristics. Additionally, professionals remained committed to the implementation, dedicating time and effort to the process and engaging in thorough evaluations, without increasing their levels of burnout. Conclusions These findings deepen the understanding of self-harm behaviors in prisons, highlighting the program STEPPS as promising approach for addressing self-harm. However, improvements in the STEPPS program are still necessary to enhance its implementation in this setting. Trial Registration NCT06297460 (ClinicalTrials.gov, retrospectively registered, 2022/01/01).